APPLICATION OF INNOVATIVE METHODS IN THE PROCESS OF LEARNING IN RUSSIAN VERBS IN FOREIGN LANGUAGE GROUPS IN HIGHER EDUCATION INSTITUTIONS (Conference Zone, 2022)
This article discusses and discusses the use of innovative methods in the study of Russian verbs in foreign language groups in higher education.